Antwort Andres Bo. von Carolstad Doctor - geweicht wasser belangend - wider einen bruder Johan. Fritzhans genant, holtzuger ordens - Karlstadt, Andreas Rudolff-Bodenstein von, ca. 1480-1541 (German books before 1601. Series II ;, 1521)
Polemical treatise by Luther's more radical colleague, Andreas Karlstadt, on the subject of Holy Water.